Kazakh-Language Business Discourse: Nature and Linguistic Features - Aimoldina А.; Akynova, D. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2020)
The paper discusses the nature and linguistic features of Kazakh-language business discourse in the context of globalization of world economic relations and the internationalization of business contacts in modern Kazakhstan. In general, Kazakh linguists agree that the business discourse in the Kazakh language is characterized by the exact use of words by meaning in the dictionary, a small number of figurative and evaluative languages, an impersonal presentation, a special cliché system, terms and stable expressions, conditional symbols and abbreviations, clear compositional structure, etc. Thus, the analysis of the history of the formation of Kazakhstan’s business discourse shows that, firstly, there is a rich and long tradition of using the Kazakh language in business communication with its own genres and language means; secondly, this tradition suspended development and, to some extent, predetermined difficulties in the functioning of Kazakhstan’s business discourse; and thirdly, the Kazakhstan business discourse, which is constantly and actively supported by a sovereign state, is currently expanding very quickly and forming its own discursive community